Prospek Pemasaran Kopi Pakuwon: Pakuwon Coffee Marketing Prospects - Ripal Padilah; Reny Sukmawani; Endang Tri Astutiningsih (Universitas Muhammadiyah Purworejo, 2023)
Pakuwon Coffee is one of the coffees produced by the Standard Testing Center for Industrial and Refreshing Plant Instruments in Kp. Pakuwon district, Parungkuda district, Sukabumi. Along with the increasing growth in coffee consumption, it is necessary to know the prospects of Pakuwon coffee as coffee that is not widely known by the general public. Based on this, this research is directed to determine the prospects for Pakuwon coffee. Based on the level of explanation, this research is a descriptive study, while based on the analysis and type of data, it is a combined qualitative and quantitative research. The results of the analysis show that Pakuwon coffee has good prospects, this can be seen from the price, product, market share, market segmentation and competitors. Pakuwon coffee has a fairly good quality based on the results of the specialty coffee association standard sensory test. From the results of this study, it is necessary to have effective promotion, record sales in each period and BPSI-TRI issue a policy to market Pakuwon Coffee products widely.